PROBLEMATICS OF CHILD MARRIAGE AND ITS CONTRIBUTION TO INCREASING STUNTING RATES - Pivit Septiary Chandra; Sonia Sischa Eka Putri; Abdiana Ilosa (Jurnal EL-RIYASAH, 2024)
Children born to mothers who marry early have a low chance of life and are at risk of nutritional problems such as shortness, thinness and malnutrition. The aim of this research is to analyze the problems regarding child marriage and its contribution to increasing stunting rates. This research uses qualitative methods and literature studies or library research, by reviewing literature books according to the theories discussed, especially regarding early marriage and stunting, as well as analyzing scientific articles. This research provides a literature review on child marriage and its contribution to increasing stunting rates in children. Marriage at this age is very vulnerable and has many risks both in terms of economics, physical and mental health. Couples who marry at child age also have insufficient and optimal knowledge in managing and fulfilling nutrition for infants and toddlers so that children born to child-aged couples will be vulnerable to stunting.